2016
DOI: 10.2352/issn.2470-1173.2016.16.hvei-103
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual image quality assessment using a normalized Laplacian pyramid

Abstract: We present an image quality metric based on the transformations associated with the early visual system: local luminance subtraction and local gain control. Images are decomposed using a Laplacian pyramid, which subtracts a local estimate of the mean luminance at multiple scales. Each pyramid coefficient is then divided by a local estimate of amplitude (weighted sum of absolute values of neighbors), where the weights are optimized for prediction of amplitude using (undistorted) images from a separate database.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 30 publications
2
101
0
Order By: Relevance
“…We also evaluate the feature similarity index (FSIM) [ZZMZ11], which uses gradient information to examine low-level features, as well as the more recent gradient magnitude similarity deviation (GMSD) [XZMB14] approach, which also focuses on local gradient similarities. Finally, we include the recently developed normalized Laplacian pyramid distance (NLP-dist), which is essentially a root mean-square error (RMSE) in a multi-scale decomposition or "normalized Laplacian" domain [LBBS16]. We note that our primary interest in this evaluation is to find an IQA that most agrees with the perceptual scores from our user study (described in the following section) on CESM data, and thus we ignore the cost of applying the IQA measures at this time.…”
Section: Image Quality Measuresmentioning
confidence: 99%
“…We also evaluate the feature similarity index (FSIM) [ZZMZ11], which uses gradient information to examine low-level features, as well as the more recent gradient magnitude similarity deviation (GMSD) [XZMB14] approach, which also focuses on local gradient similarities. Finally, we include the recently developed normalized Laplacian pyramid distance (NLP-dist), which is essentially a root mean-square error (RMSE) in a multi-scale decomposition or "normalized Laplacian" domain [LBBS16]. We note that our primary interest in this evaluation is to find an IQA that most agrees with the perceptual scores from our user study (described in the following section) on CESM data, and thus we ignore the cost of applying the IQA measures at this time.…”
Section: Image Quality Measuresmentioning
confidence: 99%
“…Similarly, being able to assess the ‘visual cost’ of a given distortion could play an important role in prosthetic design. There are already numerous metrics that can assess the perceptual quality of an image or movie based on models of the visual system (Haines and Chuang 1992, Wang et al 2004, Laparra et al 2016), but these assume no capacity for plasticity. Metrics describing the amount of ‘neurophysiologically available’ information (i.e.…”
Section: Distortions and Information Loss In Prosthetic Devicesmentioning
confidence: 99%
“…Figure 2 illustrates the components of the perceptual transform, for which we use the Normalized Laplacian Pyramid (NLP), a multi-scale nonlinear representation that mimics the operations of the retina and lateral geniculate nucleus in the human visual system. We have previously shown that distances measured between two images S x (1) Figure 2: Perceptual transform, constructed as a Normalized Laplacian Pyramid (NLP) [15]. Scene luminances S (in cd/m 2 ) are first transformed using a power function (top).…”
Section: Optimal Rendering Frameworkmentioning
confidence: 99%